The Behavioral Intention of Citizens to Finance Smart City Development in Indonesia through Civic Crowdfunding - Thaker, Mohamed Asmy Bin Mohd Thas (Global Review of Islamic Economics and Business, 2023)
In order to foster the creation of sustainable and habitable urban areas that cater to the needs of all residents, it is imperative to construct new infrastructure and concurrently ensure the upkeep and modernization of existing ones. This is where the concept of smart cities becomes instrumental, exerting a profound impact on the broader urban landscape. However, a significant challenge lies in securing the financial resources required for the development of smart cities, particularly in the midst of the current economic downturn. As a solution to this challenge, the present study proposes the implementation of an Integrated Civic Crowdfunding Model (ICCM) to finance the development of smart cities in East Java, Indonesia. Based on this proposed model, the study delves into the willingness of citizens to adopt ICCM. To achieve this, an analysis is performed utilizing Partial Least Squares on primary data collected through a survey administered to residents of East Java, specifically in Surabaya (SmartPLS). Additionally, the study assesses the model's adoption in practice by incorporating an extended Technology Acceptance Model (TAM). The study's results reveal that factors such as the perceived usefulness, perceived ease of use, and perceived benefits positively influence residents' intentions to use ICCM, thereby contributing to the advancement of smart cities in Indonesia. Furthermore, there is a favorable correlation and direct impact of perceived ease of use on the perceived utility of ICCM among citizens. These findings can serve as a foundation for the development of a specialized framework for examining other aspects of the ICCM model and devising relevant intervention strategies for the enhancement of smart cities in East Java. Originality/Value: The originality of this study lies in its introduction and application of the Integrated Civic Crowdfunding Model (ICCM) to finance the development of smart cities in East Java, Indonesia.